Health-related quality of life of adjuvant chemotherapy with S-1 versus gemcitabine for resected pancreatic cancer: Results from a randomised phase III trial (JASPAC 01). (April 2018) - Hagiwara, Yasuhiro; Ohashi, Yasuo; Uesaka, Katsuhiko; Boku, Narikazu; Fukutomi, Akira; Okamura, Yukiyasu; Konishi, Masaru; Matsumoto, Ippei; Kaneoka, Yuji; Shimizu, Yasuhiro; Nakamori, Shoji; Sakamoto, Hirohiko; et al.
Abstract: Background: Adjuvant chemotherapy with S-1 for resected pancreatic cancer demonstrated survival benefits compared with gemcitabine in the JASPAC 01 trial. We investigated the effect of these agents on health-related quality of life (HRQOL) of patients in the JASPAC 01 trial. Methods: Patients with resected pancreatic cancer were randomly assigned to receive gemcitabine (1000 mg/m 2 weekly for three of four weeks for up to six cycles) or S-1 (40, 50, or 60 mg twice daily for four of six weeks for up to four cycles). HRQOL was assessed using the EuroQol-5D-3L (EQ-5D) questionnaire at baseline, months three and six, and every 6 months thereafter. HRQOL end-points included change in EQ-5D index from baseline, responses to five items in the EQ-5D, and quality-adjusted life months up to 24 months. Results: Of randomised 385 patients, 354 patients were included in HRQOL analysis. Mean change in the EQ-5D index was similar in the S-1 and gemcitabine groups within 6 months from treatment initiation (difference, 0.024; P = 0.112), whereas corresponding mean from 12 to 24 months was better in the S-1 group than in the gemcitabine group (difference, 0.071; P < 0.001). Problems in mobility and pain/discomfort were also less frequent in the S-1 group than in the gemcitabine group in that period. Quality-adjusted life months were longer in the S-1 group than in the gemcitabine group ( P < 0.001). Conclusion: Adjuvant chemotherapy with S-1 does not improve HRQOL within 6 months from treatment initiation but does improve HRQOL thereafter and quality-adjusted life months. Clinical trial registration number: UMIN000000655 at UMIN CTR. Highlights: Health-related quality of life (HRQOL) in the JASPAC 01 trial was analysed. The trial compared adjuvant S-1 with gemcitabine for resected pancreatic cancer. HRQOL within 6 months was similar between the two treatments. HRQOL from 12 to 24 months was better with S-1 than with gemcitabine. Quality-adjusted life months were longer with S-1 than with gemcitabine.